Preparation method of iron-aluminum hierarchical porous material

By using vacuum sublimation of magnesium nitride and high-temperature decomposition of pores in the porous materials of iron and aluminum intermetallic compound, the hollow structure of egg shell is formed, which solves the problems of low porosity and magnesium reaction of existing materials, and achieves the effects of high porosity and high filtration efficiency.

CN119870469AActive Publication Date: 2025-04-25WUHAN UNIV OF TECH
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202510377183.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-28
Publication Date
2025-04-25
Estimated Expiration
2045-03-28

AI Technical Summary

Technical Problem

The porous materials of existing iron-aluminum intermetallic compounds have low porosity, low filtration efficiency, and magnesium elements are prone to react with iron and aluminum elements, resulting in a decline in material performance.

Method used

By mixing iron powder, aluminum powder with fused paraffin and stirring, magnesium nitride powder is added, molding and vacuum sintering is carried out, and pores are made by vacuum sublimation of magnesium nitride and high-temperature decomposition to form a hollow multi-stage pore structure of egg shells.

Benefits of technology

The porosity of porous iron-aluminum intermetallic compound materials is significantly improved, the filtration efficiency is enhanced, and the weight of the material is reduced, avoiding the residual influence of magnesium.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119870469A_ABST
    Figure CN119870469A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of alloy materials, and provides a preparation method of an iron-aluminum hierarchical porous material, which comprises the following steps: mixing and stirring iron powder, aluminum powder and molten paraffin, then adding magnesium nitride powder, uniformly stirring, after the molten paraffin is cooled and solidified, crushing, and then putting into a mold for compression molding to obtain the iron-aluminum hierarchical porous material. And then carrying out vacuum sintering on the formed pressed blank to obtain the iron-aluminum series hierarchical porous material. The particle size of the magnesium nitride powder is larger than that of the iron powder and the aluminum powder. Magnesium nitride particles are wrapped by iron powder particles and aluminum powder particles by using a paraffin mixed solution wrapping method, a series of intermetallic compounds are formed between iron and aluminum in the sintering process, and magnesium nitride can be sublimated and decomposed through gaps in the intermetallic compounds, so that the heat conductivity of the magnesium nitride is improved, and the service life of the magnesium nitride is prolonged. And therefore, an egg shell type structure which takes the iron-aluminum metal compound as a shell and is hollow inside is formed in a microcosmic form, the porosity of the porous material can be further improved, and the weight of the material is reduced at the same time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of alloy materials, and in particular to a method for preparing an iron-aluminum multi-level porous material. Background Art

[0002] During the operation of the car, the exhaust pipe contains a large amount of high-temperature dust, sulfur and corrosive gases, and the iron-aluminum intermetallic compound has excellent high-temperature anti-oxidation and anti-sulfurization properties, which can adapt to the extreme working environment in the automobile exhaust pipe. At the same time, the iron-aluminum intermetallic compound has good ductility and welding properties at room temperature, which can adapt to the production and assembly of automobile exhaust pipe filter materials. Therefore, the porous material based on the iron-aluminum intermetallic compound can meet the filtration separation and mechanical performance requirements of automobile exhaust pipe filter materials under extreme high temperature conditions.

[0003] The preparation methods of porous iron-aluminum intermetallic compound materials mainly include reaction synthesis method, high-temperature self-propagating synthesis method and pore-forming agent method. The reaction synthesis method has the characteristics of long preparation cycle, high energy consumption and low open porosity of the prepared porous materials, which is generally around 50%. The open porosity of the porous material prepared by the high-temperature self-propagating synthesis method is around 60%; in addition, the reaction of this method is more violent, the reaction is more difficult to control and the prepared porous material is prone to cracks and deformation. The open porosity of the porous iron-aluminum intermetallic compound material prepared by the pore-forming agent method is around 50%, which has no significant advantages over the above two methods. In addition, this method cannot ensure the complete removal of the pore-forming agent, and the residue of the pore-forming agent may affect the performance of the porous material.

[0004] The existing method of preparing iron-aluminum intermetallic compound porous materials by sintering iron, aluminum and magnesium ternary metal powders (CN112853139A) is that magnesium easily reacts with iron and aluminum, resulting in a decrease in the performance of the porous material. Therefore, a method for preparing an iron-aluminum multi-level porous material with higher porosity and better filtration efficiency is needed. Summary of the invention

[0005] In view of this, the present invention proposes a method for preparing an iron-aluminum multi-level porous material with higher porosity and better filtration efficiency.

[0006] The technical solution of the present invention is achieved as follows: The present invention provides a method for preparing an iron-aluminum multi-level porous material, comprising the following steps: The iron powder, aluminum powder and molten paraffin are mixed and stirred, and then magnesium nitride powder is added and stirred evenly. After the molten paraffin is cooled and solidified, it is crushed and then put into a mold for compression molding. Subsequently, the molded compact is vacuum sintered to obtain an iron-aluminum multi-level porous material; the particle size of the magnesium nitride powder is larger than that of the iron powder and the aluminum powder.

[0007] On the basis of the above technical solution, preferably, the compression molding is performed by conventional compression molding or cold isostatic pressing, and the compression molding pressure is less than 50 MPa.

[0008] On the basis of the above technical solution, preferably, the vacuum degree of vacuum sintering is less than 0.01Pa.

[0009] The present invention utilizes iron powder and aluminum powder to wrap magnesium nitride particles, and completes eggshell hollow pore formation through diffusion / reaction pore formation during the sintering process and vacuum sublimation and high-temperature decomposition pore formation of magnesium nitride during the sintering process, thereby further improving the porosity of the porous iron-aluminum intermetallic compound material and reducing the weight of the porous material, thereby obtaining a high-porosity multi-level porous iron-aluminum intermetallic compound material.

[0010] The present invention synergistically utilizes the following three approaches and a structure to increase the porosity of the porous iron-aluminum intermetallic compound material: The pores are formed by using the asymmetric diffusion of iron and aluminum elements in the solid-solid state and the solid-liquid state to consume aluminum. Vacuum sublimation of magnesium nitride. Magnesium nitride will sublime in a high-temperature vacuum environment, achieving gas phase removal and pore formation of magnesium nitride; High-temperature decomposition of magnesium nitride. Under high-temperature vacuum conditions, magnesium nitride will decompose into magnesium vapor, nitrogen groups, and nitrogen gas. Nitrogen groups and nitrogen gas can escape under vacuum conditions, while magnesium vapor will adhere to the furnace wall or condense and deposit in the low-temperature area of ​​the furnace tube, thus achieving cracking, removal, and pore formation of magnesium nitride. The pore structure is formed by the sublimation and decomposition of magnesium nitride particles wrapped by iron and aluminum powder.

[0011] On the basis of the above technical solution, preferably, the iron powder and aluminum powder are Fe 1-x -Al x The ingredients are prepared in a ratio of atomic percentage, where x is 22.5%~76.5%.

[0012] From the Fe-Al binary phase diagram, it can be seen that when the atomic percentage of aluminum is 22.5%~76.5%, it can form a series of iron-aluminum intermetallic compounds with iron, such as FeAl, FeAl 2 、FeAl 3 , Fe 2 Al 5 and Fe 3 Al, etc. Therefore, the initial atomic ratio of the two elements in the Fe-Al system is Fe 1-x -Al x , where x is the atomic percentage, and the value range of x is 22.5%~76.5%.

[0013] On the basis of the above technical solution, preferably, the mass ratio of the iron-aluminum powder mixture to the molten paraffin is 2:1-6:1, and the mass ratio of the magnesium nitride powder to the iron-aluminum powder mixture is 2:5-4:5.

[0014] The iron and aluminum powders with good proportions are mixed and stirred with the paraffin solution at a mass ratio of 2:1~6:1, and the magnesium nitride powder particles and the iron and aluminum powders added to the paraffin solution are weighed at a mass ratio of 2:5~4:5 and mixed into the paraffin solution for stirring. After the paraffin solution is cooled, it is crushed to obtain structural particles with magnesium nitride powder particles coated with iron and aluminum metal particles. The coated structural particles are then placed in a sintering mold for compression molding and subsequent sintering.

[0015] On the basis of the above technical solution, preferably, the particle size of the iron powder and the aluminum powder is 1-100 μm, and the particle size of the magnesium nitride powder is 500-1000 μm.

[0016] On the basis of the above technical solution, preferably, the vacuum sintering method comprises the following steps: S1, first raise the temperature to a temperature above the boiling point of paraffin, and keep the temperature at this temperature for more than 1 hour; S2, then continue to heat up to the temperature of solid diffusion of iron and aluminum, and keep the reaction at this temperature for 0.5h~5h; S3, then continue to raise the temperature to above the melting point of aluminum, but not exceeding the temperature at which magnesium nitride begins to sublime, and keep the reaction at this temperature for 0.5h~3h; S4, then continue to raise the temperature to the sublimation and decomposition temperature of magnesium nitride, and keep the reaction at this temperature for 1 to 6 hours.

[0017] On the basis of the above technical solution, preferably, in step S1, the temperature is raised to 400-500°C at a heating rate of 1°C / min-5°C / min, so that the paraffin wax is completely volatilized, and the iron and aluminum shell structures are initially stabilized by diffusion between the iron and aluminum particles; Based on the above technical solution, preferably, in step S2, the temperature is raised to 500-660°C at a heating rate of 1°C / min-5°C / min. 3 N 2 In the ternary system, different ratios of the two component elements of iron and aluminum result in different temperature points being selected within the solid-state diffusion and reaction temperature zone for different insulation times.

[0018] On the basis of the above technical solution, preferably, in step S3, the temperature is raised to 660-700°C at a heating rate of 1°C / min-5°C / min, so that the remaining aluminum in the solid state is completely transformed into liquid aluminum, and the liquid aluminum quickly wraps the iron particles and reacts with them to form a series of iron-aluminum intermetallic compounds. This process ensures that the sintered billet no longer contains elemental aluminum, while further improving the porosity, avoiding the reaction of elemental aluminum with magnesium vapor, nitrogen groups and nitrogen generated by the decomposition of magnesium nitride, thereby avoiding affecting the composition and properties of the prepared multi-level porous iron-aluminum intermetallic compound material. At the same time, the iron-aluminum intermetallic compound formed in this process will wrap the magnesium nitride particles like an eggshell.

[0019] Based on the above technical solution, preferably, in step S4, the temperature is raised to 700-1100°C at a heating rate of 1°C / min-10°C / min. Specifically, in this step, multiple insulation temperatures can be selected within the temperature range for different insulation times, and the specific situation can be determined according to the Fe-Al-Mg 3 N 2 The content of magnesium nitride in the ternary system. For example, in the preferred embodiment 1 of the present invention, only one temperature point is selected for the insulation operation in the magnesium nitride vacuum sublimation and high temperature decomposition temperature zone, and the temperature point must be higher than 800°C. At this stage, the sublimation and decomposition behaviors of magnesium nitride occur simultaneously. In the preferred embodiments 2 and 3 of the present invention, two temperature points are selected for insulation operation. The first temperature point should be in the range of 700-800°C, where the sublimation behavior of magnesium nitride mainly occurs; the second temperature point should be in the range of 800-1100°C, and the behavior occurring at this temperature point depends on the insulation time of the first temperature point. If the insulation time at the first temperature point is not long enough, and the magnesium nitride in the ternary system is not completely sublimated into the furnace tube, then the sublimation and decomposition behaviors of magnesium nitride will occur simultaneously at this temperature point; if the insulation time at the first temperature point is long enough, and the magnesium nitride in the ternary system is completely sublimated into the furnace tube, then only the decomposition behavior of magnesium nitride will occur at this temperature point. At the same time, due to the sublimation and decomposition of magnesium nitride in this process, a hollow multi-level porous material with an iron-aluminum intermetallic compound as an outer shell is gradually formed, thereby further improving the porosity of the material.

[0020] On the basis of the above technical scheme, preferably, it also includes heating to 900~1100℃ at a heating rate of 1℃ / min~10℃ / min, and keeping warm for 1~2h. Whether this step needs to be implemented should be determined according to the selection of the temperature point and the insulation time point in step S4 and the composition of the prepared iron-aluminum intermetallic compound. If the insulation has been carried out for more than 2h in the temperature range of 900~1100℃ in step S4, this step may not be implemented. If the insulation operation in the above temperature zone is not completed, the temperature is continued to be raised to 900~1100℃ at a heating rate of 1℃ / min~10℃ / min, and kept warm for 1~2h. In this temperature zone, the high-temperature phase transformation will be completed to generate the desired iron-aluminum intermetallic compound and the homogenization of the composition and structure will be completed. The multi-level porous iron-aluminum intermetallic compound material finally obtained has an open porosity of more than 60%, a total porosity of more than 65%, and a pore size range of 1~300μm. Specifically, in preferred embodiments 1 and 2 of the present invention, the heat preservation operation in this step is not performed; whereas in preferred embodiment 3 of the present invention, the heat preservation operation in this step is performed.

[0021] The principle of the present invention is to use paraffin wax mixed with iron and aluminum powder particles to wrap the magnesium nitride powder particles with larger particle size, and at 500-660°C, the lower boiling point of paraffin wax is used to evaporate and the solid diffusion and reaction between iron and aluminum are used to obtain a ternary system of magnesium nitride particles coated with only iron and aluminum. 3 N 2 In the system, below 700°C, there is no chemical reaction between magnesium nitride and the two components of iron and aluminum. This stage is mainly dominated by diffusion and reaction between the two components of iron and aluminum. As we all know, the melting point of aluminum is about 660°C. When the temperature of the ternary system rises to near the melting point of aluminum (between 660 and 700°C), the remaining aluminum in the solid state will all form liquid aluminum to wrap the iron particles, and quickly react with the surrounding iron particles to generate a series of iron-aluminum intermetallic compounds. After the above-mentioned stages of reaction, the elemental aluminum in the ternary system disappears, and only iron-aluminum intermetallic compounds exist in the system. At the same time, the space originally occupied by the aluminum powder particles forms a void.

[0022] Secondly, the present invention also relates to vacuum sublimation and high temperature decomposition pore formation of magnesium nitride, which further improves the porosity of porous iron-aluminum intermetallic compound materials. It is reported that magnesium nitride begins to sublimate at about 700°C. When the temperature of the ternary system is increased to above 700°C, magnesium nitride will undergo sublimation behavior in a high vacuum environment, realize gas phase dealloying to complete pore formation, and further improve the porosity while realizing the removal of magnesium nitride. In addition, magnesium nitride will undergo decomposition behavior above 800°C to generate magnesium vapor, nitrogen groups and nitrogen. In a high vacuum environment, nitrogen groups and nitrogen can escape from the furnace tube, and magnesium vapor will move to the high vacuum area in the furnace and deposit in the low temperature area of ​​the inner wall of the furnace tube, thereby ensuring that magnesium vapor does not crystallize and deposit on the sample surface. When the temperature of the ternary system is increased to above 800°C, magnesium nitride will undergo decomposition behavior in a high vacuum environment, realize the cracking and removal of magnesium nitride to form pores, and continue to improve the porosity while realizing the further removal of magnesium nitride. Through the two removal methods of vacuum sublimation and high temperature decomposition, the removal of magnesium nitride can be fully guaranteed, and the residue of pore-forming agent and its influence on the performance of the obtained multi-level porous iron-aluminum intermetallic compound material can be avoided. Among them, the magnesium gas produced by decomposition can react with the residual oxygen in the furnace environment to deoxygenate, thereby reducing the oxidation degree of the material and improving the material performance; the nitrogen produced by decomposition can be used as a protective atmosphere, thereby further purifying the furnace environment.

[0023] In addition, the present invention uses a paraffin mixed solution wrapping method to wrap iron powder particles and aluminum powder particles to wrap magnesium nitride particles. During the sintering process, a series of intermetallic compounds are formed between iron and aluminum, and magnesium nitride can be sublimated and decomposed through the voids in the intermetallic compounds, thereby forming an eggshell-like structure with the iron-aluminum intermetallic compound as the outer shell and a hollow interior in the microscopic view, thereby further improving the porosity of the porous material while reducing the weight of the material.

[0024] On the basis of the above technical solution, preferably, the iron-aluminum multi-level porous material is a hollow structure, the open porosity is 60% to 62%, and the total porosity is 65% to 70%.

[0025] The preparation method of the iron-aluminum multi-level porous material of the present invention has the following beneficial effects compared with the prior art: The present invention makes full use of the hollow structure of the eggshell-like iron-aluminum intermetallic compound left by the sublimation and decomposition of magnesium nitride, and has a hole-in-hole structural feature. On the premise of meeting the filterability requirements, the porosity can be further improved while reducing the weight to achieve lightweight.

[0026] In the stage below the decomposition temperature of magnesium nitride, the diffusion / reaction pore formation of iron and aluminum elements is fully utilized. The through holes formed between the iron powder particles in this stage will serve as the sublimation channel of magnesium nitride in the high temperature stage and the escape channel of the decomposition products of magnesium nitride. In addition, aluminum is fully consumed in this stage to avoid the reaction of the residual elemental aluminum with the decomposition products of magnesium nitride to affect the composition and performance of the multi-level porous iron-aluminum intermetallic compound material.

[0027] The present invention makes full use of the stable chemical properties of magnesium nitride and the properties of magnesium nitride that are easy to sublimate and decompose, and avoids the ternary Fe-Al-Mg 3 N 2 The residual magnesium nitride in the system is conducive to the preparation of pure binary multi-level porous iron-aluminum intermetallic compound materials with high porosity.

[0028] The present invention utilizes the characteristic that magnesium has a high saturated vapor pressure at high temperature. During the sintering process, it avoids reacting with iron and aluminum in the stage of diffusion / reaction of iron and aluminum, avoids the crystallization and deposition of magnesium produced by the decomposition of magnesium nitride on the sample surface, and avoids the residue of magnesium element and its influence on the composition and performance of the multi-level porous iron-aluminum intermetallic compound material.

[0029] The present invention fully utilizes the magnesium gas generated by the decomposition of magnesium nitride to react with the residual oxygen in the furnace tube, and fully utilizes the nitrogen generated by the decomposition of magnesium nitride as a protective gas, further purifies the sample preparation environment in the furnace tube, and further reduces the oxidation degree of the sample preparation.

[0030] The present invention makes full use of a series of intermetallic compounds formed by iron and aluminum and a composite material formed by elemental iron. The composite material has both the elasticity and plasticity of metal materials and the heat resistance and corrosion resistance of ceramic materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0032] Figure 1 This is a schematic diagram of the eggshell structure composed of iron, aluminum and magnesium nitride before firing in Example 1; Figure 2 This is a schematic diagram of the cross-sectional structure of the iron-aluminum multi-level porous material obtained in Example 1; Figure 3 This is a scanning electron microscope photograph of the cross section of the iron-aluminum multi-level porous material prepared in Example 1.

[0033] In the figure: 1 is a magnesium nitride powder particle; 2 is a mixed shell of iron powder and aluminum powder particles; 3 is a cavity left after the sublimation and decomposition of the magnesium nitride particles; 4 is an iron-aluminum metal compound; 5 is a cavity left after the complete diffusion reaction of the aluminum particles. DETAILED DESCRIPTION

[0034] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] Example 1 Embodiment 1 of the present invention provides a method for preparing an iron-aluminum multi-level porous material, which specifically comprises the following steps: (1) The structure of Fe-Al binary powder wrapped powder particles was obtained by paraffin coating, wherein the particle size of magnesium nitride powder was 500 μm, and the particle sizes of iron powder and aluminum powder were both 30 μm. In order to obtain a multi-level porous iron-aluminum intermetallic compound material with the composition of FeAl, the powder mass was proportioned according to the atomic ratio of 50% Fe-50% Al, that is, the atomic ratio of iron to aluminum was 1:1, and the iron and aluminum powders with the proportioned ratio were mixed and stirred with the paraffin solution at a mass ratio of 7:2, and the magnesium nitride powder particles and the iron and aluminum powders added to the paraffin solution were weighed at a mass ratio of 3:5 and mixed into the paraffin solution and stirred. After the paraffin solution was cooled, it was crushed to obtain the structure particles with iron and aluminum metal particles coated with magnesium nitride powder particles, and then the coated structure particles were placed in a sintering mold and molded at a pressure of 15 MPa.

[0036] (2) The pressed green sheet is placed in a tubular furnace for vacuum sintering at a heating rate of 5°C / min to 450°C and kept at this temperature for 1 hour to allow the paraffin to completely evaporate and initially stabilize the iron and aluminum shell structure through diffusion between the iron and aluminum particles.

[0037] (3) Raise the temperature to 600℃ at a rate of 5℃ / min and keep it at this temperature for 5h. Since the intrinsic diffusion coefficient of aluminum is much larger than that of iron, aluminum atoms will continue to diffuse to the surrounding iron particles at this stage. The aluminum atoms diffused to the iron particles will first dissolve into the iron. When the aluminum atoms reach the solid solubility limit in the iron matrix, aluminum reacts with iron (aluminum) to form a series of intermetallic compounds. A large number of vacancies will be formed around the aluminum particles at this stage, and the aggregation of vacancies will form pores.

[0038] (4) Continue heating the temperature to 660°C at a heating rate of 1°C / min and keep the temperature for 3 hours. At this time, the remaining solid aluminum in step (3) will all turn into liquid, and the liquid aluminum will quickly wrap the surrounding iron particles. At this time, the intrinsic diffusion coefficient of iron is greater than the intrinsic diffusion coefficient of aluminum. The iron particles diffuse into the aluminum solution in large quantities, and Kirkendall cavities are generated inside the iron particles. The aluminum reacts with the iron particles around it and is completely consumed. At this stage, the positions originally occupied by the aluminum particles are all turned into pores, and the porosity is further improved. At the same time, the formed iron-aluminum intermetallic compound will wrap the magnesium nitride particles.

[0039] (5) Continue heating at a rate of 5°C / min to 1000°C and keep warm for 1h. During this stage, the sublimation and decomposition of magnesium nitride will occur simultaneously. 3 N 2 Part of the magnesium nitride in the ternary system will sublime into the furnace tube along the openings formed in steps (3) and (4). In addition, since the temperature has exceeded the temperature at which magnesium nitride begins to decompose, the magnesium nitride contained in the compact and the magnesium nitride sublimated into the furnace tube will eventually decompose to form magnesium vapor, nitrogen groups and nitrogen gas. The nitrogen groups and nitrogen gas will escape under vacuum, while the magnesium vapor will be deposited at both ends of the furnace tube. This stage can ensure the complete removal of magnesium nitride, so pores will be formed at the positions originally occupied by magnesium nitride particles, and the porosity of the compact will be further improved. In addition, this stage can also complete the high-temperature phase change and achieve the homogenization of the composition and structure; finally, an eggshell-like multi-level porous iron-aluminum intermetallic compound material with a composition of FeAl, an open porosity of 60%, and a total porosity of 65% is obtained.

[0040] Figure 1 Shown is a schematic diagram of the eggshell structure formed by iron, aluminum, and magnesium nitride before firing in this embodiment.

[0041] Figure 2 The figure shows a schematic diagram of the cross-sectional structure of the iron-aluminum multi-level porous material prepared in this embodiment. It can be seen from the figure that the prepared iron-aluminum multi-level material contains a large number of pores, which are mainly pores left after the sublimation and decomposition of magnesium nitride with larger particles, and pores left after the diffusion and reaction of iron and aluminum.

[0042] Figure 3 The figure shows a scanning electron microscope photograph of the interface of the iron-aluminum series multi-level porous material prepared in this embodiment. It can be seen from the figure that the prepared iron-aluminum series multi-level porous material has a large number of holes.

[0043] Example 2 Embodiment 2 of the present invention provides a method for preparing an iron-aluminum multi-level porous material, which specifically comprises the following steps: (1) The structure of Fe-Al binary powder wrapped powder particles was obtained by paraffin coating, wherein the particle size of magnesium nitride powder was 800 μm, and the particle sizes of iron powder and aluminum powder were both 60 μm. 3 The multi-level porous iron-aluminum intermetallic compound material is prepared according to the atomic ratio of 23.5%Fe-76.5%Al, that is, the atomic ratio of iron to aluminum is 23.5:76.5. The iron and aluminum powders with good proportions are mixed and stirred with the paraffin solution at a mass ratio of 2:1. The magnesium nitride powder particles and the iron and aluminum powders added to the paraffin solution are weighed and mixed into the paraffin solution at a mass ratio of 2:5 and stirred. After the paraffin solution is cooled and crushed, the structural particles with iron and aluminum metal particles coated with magnesium nitride powder particles can be obtained. The coated structural particles are then placed in a sintering mold and molded at a pressure of 15MPa.

[0044] (2) The pressed green sheet is placed in a tubular furnace for vacuum sintering at a heating rate of 1°C / min to 400°C and kept at this temperature for 1 hour to allow the paraffin to completely evaporate and initially stabilize the iron and aluminum shell structure through diffusion between the iron and aluminum particles.

[0045] (3) Raise the temperature to 500°C at a rate of 1°C / min and keep it at this temperature for 0.5h. Since the intrinsic diffusion coefficient of aluminum is much larger than that of iron, aluminum atoms will continue to diffuse to the surrounding iron particles at this stage. The aluminum atoms diffused to the iron particles will first dissolve into the iron. When the aluminum atoms reach the solubility limit in the iron matrix, aluminum reacts with iron (aluminum) to form a series of intermetallic compounds. A large number of vacancies will be formed around the aluminum particles at this stage, and the aggregation of vacancies will form pores.

[0046] (4) Continue heating the temperature to 670°C at a rate of 5°C / min and keep it at that temperature for 1 hour. At this time, the remaining solid aluminum in step (3) will all turn into liquid, and the liquid aluminum will quickly wrap around the iron particles and react with the surrounding iron particles to be completely consumed. At this stage, the positions originally occupied by the aluminum particles will all become pores, and the porosity will be further increased. At the same time, the formed iron-aluminum intermetallic compound will wrap around the magnesium nitride particles.

[0047] (5) Continue heating up to 700°C at a heating rate of 5°C / min and keep at this temperature for 2 hours. At this stage, the magnesium nitride in the green compact begins to sublime, and the magnesium nitride sublimates into the furnace tube along the openings formed in steps (3) and (4). At this stage, pores are formed at the positions originally occupied by the magnesium nitride particles, and the porosity of the green compact is further increased.

[0048] (6) Continue to heat up to 1050℃ at a heating rate of 10℃ / min and keep it at this temperature for 1.5h. At this stage, magnesium nitride will decompose to form magnesium vapor, nitrogen groups and nitrogen gas. Nitrogen groups and nitrogen gas will escape in a vacuum environment, while magnesium vapor will be deposited at both ends of the furnace tube. This stage can further remove magnesium nitride to ensure that magnesium nitride will not remain in the compact. This stage can achieve the improvement of porosity while also achieving the homogenization of composition and structure. The final composition is FeAl 3 , an eggshell-like multi-level porous iron-aluminum intermetallic compound material with an open porosity of 60% and a total porosity of 70%.

[0049] Example 3 Embodiment 3 of the present invention provides a method for preparing an iron-aluminum multi-level porous material, which specifically comprises the following steps: (1) The structure of Fe-Al binary powder wrapped powder particles was obtained by paraffin coating, wherein the particle size of magnesium nitride powder was 1000 μm, and the particle sizes of iron powder and aluminum powder were both 100 μm. 3 The Al multi-level porous iron-aluminum intermetallic compound material is mixed in powder mass according to the atomic ratio of 77.5%Fe-22.5%Al, that is, the atomic ratio of iron to aluminum is 77.5:22.5. The iron and aluminum powders with good proportions are mixed and stirred with the paraffin solution at a mass ratio of 6:1. The magnesium nitride powder particles and the iron and aluminum powders added to the paraffin solution are weighed at a mass ratio of 4:5 and mixed into the paraffin solution for stirring. After the paraffin solution is cooled and crushed, the structural particles with iron and aluminum metal particles coated with magnesium nitride powder particles can be obtained. The coated structural particles are then placed in a sintering mold and molded at a pressure of 15MPa. (2) The pressed green sheet is placed in a tubular furnace for vacuum sintering at a heating rate of 3°C / min to 500°C and kept at this temperature for 1 hour to allow the paraffin to completely evaporate and initially stabilize the iron and aluminum shell structure through diffusion between the iron and aluminum particles.

[0050] (3) The pressed green sheet is placed in a tubular furnace for vacuum sintering. First, the temperature is raised to 660°C at a rate of 5°C / min and kept at this temperature for 1.5 hours. Since the intrinsic diffusion coefficient of aluminum is much larger than that of iron, aluminum atoms will continue to diffuse to the surrounding iron particles at this stage. The aluminum atoms diffused to the iron particles will first dissolve into the iron. When the aluminum atoms reach the solubility limit in the iron matrix, aluminum reacts with iron (aluminum) to form a series of intermetallic compounds. A large number of vacancies will be formed around the aluminum particles at this stage, and the aggregation of vacancies will form pores.

[0051] (4) Continue heating the temperature at a rate of 3°C / min to 700°C and keep it at this temperature for 1.5 hours. At this time, the remaining aluminum in step (3) will all become liquid, and the liquid aluminum will quickly react with the iron particles around it and be completely consumed. At this stage, the positions originally occupied by aluminum particles will all become pores, and the porosity will be further increased. At the same time, the formed iron-aluminum intermetallic compound will wrap around the magnesium nitride particles.

[0052] (5) Continue heating up to 750°C at a heating rate of 1°C / min and keep the temperature for 3 hours. At this stage, the magnesium nitride in the green compact begins to sublime, and the magnesium nitride sublimates into the furnace tube along the openings formed in steps (3) and (4). At this stage, pores are formed at the positions occupied by the magnesium nitride particles, and the porosity of the green compact is further increased.

[0053] (6) Continue heating the temperature to 850°C at a heating rate of 5°C / min and keep it at this temperature for 2 hours. At this stage, magnesium nitride will decompose to form magnesium vapor, nitrogen groups and nitrogen gas. Nitrogen groups and nitrogen gas will escape under vacuum, while magnesium vapor will be deposited at both ends of the furnace tube. This stage can further remove magnesium nitride and ensure that magnesium nitride will not remain in the compact. In addition, this stage can further improve the porosity of the multi-level porous iron-aluminum intermetallic compound material.

[0054] (7) Continue heating up to 1100°C at a rate of 8°C / min and keep warm for 1h. This stage mainly completes the high-temperature phase transition and achieves the homogenization of composition and structure. The final composition is Fe 3 Al, an eggshell-like multi-level porous iron-aluminum intermetallic compound material with an open porosity of 62% and a total porosity of 70%.

[0055] Comparative Example 1 Compared with Example 1, the atomic ratio of iron to aluminum is 9:1, and the comparative example 1 specifically comprises the following steps: (1) The structure of Fe-Al binary powder coated powder particles is obtained by paraffin coating, wherein the particle size of magnesium nitride powder is 500μm, and the particle size of iron powder and aluminum powder are both 30μm. According to the atomic ratio of 90%Fe-10%Al, that is, the atomic ratio of iron to aluminum is 9:1, the iron and aluminum powders with good proportions are mixed and stirred with the paraffin solution at a mass ratio of 7:2, and the magnesium nitride powder particles and the iron and aluminum powders added to the paraffin solution are weighed at a mass ratio of 3:5 and mixed into the paraffin solution and stirred. After the paraffin solution is cooled, it is crushed to obtain the structure particles with iron and aluminum metal particles coated with magnesium nitride powder particles, and then the coated structure particles are placed in a sintering mold and molded at a pressure of 15MPa.

[0056] (2) The pressed green sheet was placed in a tubular furnace for vacuum sintering, the temperature was raised to 450°C at a heating rate of 5°C / min, and the temperature was kept at that temperature for 1 h.

[0057] (3) Raise the temperature to 600°C at a rate of 5°C / min and keep at this temperature for 5 h.

[0058] (4) Continue to increase the temperature at a rate of 1°C / min to 660°C and keep it at this temperature for 3 h.

[0059] (5) Continue to increase the temperature at a rate of 5°C / min to 1000°C and keep it at that temperature for 1 h.

[0060] The final composition is Fe 3 Al and Fe, porous material with an open porosity of 33% and a total porosity of 46%.

[0061] In Comparative Example 1, the atomic ratio of iron to aluminum is greatly biased towards iron (9:1). On the one hand, the number of aluminum atoms is insufficient, and they cannot effectively participate in diffusion and reaction. The formation of vacancies is relatively small, and the number and scale of pore generation will be significantly limited, which ultimately leads to a decrease in the overall porosity of the material. On the other hand, when the iron content is too high and the aluminum content is relatively low, iron particles occupy the main component, and their diffusion effect is weakened, while liquid aluminum is not enough to effectively promote the large-scale generation of voids, thereby reducing the porosity. Part of the iron exists in the form of a free element, which not only reduces the homogenization degree of the material, but also reduces the effective diffusion process involved in pore formation. At the same time, the connection strength between the incompletely formed intermetallic compounds is relatively small, resulting in the collapse of the voids, destroying the "eggshell" multi-level pore structure, and thus affecting the porosity.

[0062] Comparative Example 2 Comparative Example 2 Compared with Example 1, the atomic ratio of iron to aluminum is 1:9, and the preparation method of the iron-aluminum porous material specifically includes the following steps: (1) The structure of Fe-Al binary powder wrapped powder particles is obtained by paraffin coating, wherein the particle size of magnesium nitride powder is 500μm, and the particle size of iron powder and aluminum powder are both 30μm. The powder mass ratio is made according to the atomic ratio of 10%Fe-90%Al, that is, the atomic ratio of iron to aluminum is 1:9, and the iron and aluminum powders with the good ratio are mixed and stirred with the paraffin solution at a mass ratio of 7:2. The magnesium nitride powder particles and the iron and aluminum powders added to the paraffin solution are weighed at a mass ratio of 3:5 and mixed into the paraffin solution and stirred. After the paraffin solution is cooled, it is crushed to obtain the structure particles with iron and aluminum metal particles coated with magnesium nitride powder particles. Then, the coated structure particles are placed in a sintering mold and molded at a pressure of 15MPa.

[0063] (2) The pressed green compact was placed in a tubular furnace for vacuum sintering, and the temperature was increased to 450°C at a heating rate of 5°C / min and kept at this temperature for 1 h.

[0064] (3) Raise the temperature to 600°C at a rate of 5°C / min and keep at this temperature for 5 h.

[0065] (4) Continue to increase the temperature at a rate of 1°C / min to 660°C and keep it at this temperature for 3 h.

[0066] (5) Continue to increase the temperature at a rate of 5°C / min to 1000°C and keep it at that temperature for 1 h.

[0067] The final composition is FeAl 3 and Al, a porous material with an open porosity of 28% and a total porosity of 42%.

[0068] In Comparative Example 2, when aluminum is too abundant, the diffusion process tends to be saturated, resulting in a decrease in the diffusion rate and a decrease in the amount of vacancies generated around the aluminum particles. At the same time, since the insulation temperature exceeds the melting point of aluminum, aluminum will quickly fill the remaining voids in liquid form, which directly reduces the number and size of pores. In addition, due to the low iron content, the process of aluminum solid solution and reaction with iron to form intermetallic compounds during diffusion is limited, which further reduces the generation of pores. In addition, when the iron content is too low, the number of iron particles available for diffusion is significantly reduced, and the Kirkendall voids inside the corresponding subway particles are reduced, and the overall number and connectivity of pores in the material are greatly affected.

[0069] At high temperatures, magnesium nitride particles will sublime and decompose, and the positions originally occupied by magnesium nitride particles will be transformed into pores. However, this process requires the formation of a large number of open channels to provide a path for magnesium nitride sublimation. In Comparative Example 2, the iron content is relatively low, and the material as a whole lacks sufficient intermetallic compound skeleton and structural support. The generated pore size and connectivity are insufficient, and the path to form pores is blocked, resulting in incomplete removal of magnesium nitride, thereby reducing porosity.

[0070] In addition, in Comparative Example 2, the excess of aluminum and the scarcity of iron resulted in insufficient and unevenly distributed intermetallic compounds. When the amount of intermetallic compounds is small, it is impossible to provide a relatively uniform "eggshell" multi-level pore structure as in Example 1. Excess aluminum easily forms a thin film of liquid covering at high temperature, and this liquid aluminum covering may fill the existing pores and cause the collapse of some pores, further reducing the porosity.

[0071] Comparative Example 3 The preparation method of the iron-aluminum porous material of Comparative Example 3 specifically comprises the following steps: (1) Three kinds of powders, namely elemental iron powder, elemental aluminum powder and magnesium nitride powder, were selected as the original powders, and their particle sizes were all 30 μm. In order to obtain a porous iron-aluminum intermetallic compound material with the composition of FeAl, the ((50%Fe-50%Al)-30%Mg 3 N 2), that is, the atomic ratio of iron to aluminum is 1:1, and the ratio of the total number of iron and aluminum to magnesium nitride molecules is 7:3. The weights of the three powders are calculated and the powders are weighed respectively. Then, the materials are mixed in a vacuum mixing tank for 8 hours. Finally, the evenly mixed ternary powder is molded at a pressure of 15MPa.

[0072] (2) The pressed green compact is placed in a tubular furnace for vacuum sintering. First, the temperature is raised to 600°C at a rate of 5°C / min and kept at this temperature for 5 h.

[0073] (3) Continue to increase the temperature at a rate of 1°C / min to 660°C and keep it at this temperature for 3 h.

[0074] (4) The temperature is continued to be raised to 1000°C at a heating rate of 5°C / min and kept at this temperature for 1 h, and finally a porous iron-aluminum intermetallic compound material with a composition of FeAl, an open porosity of 50%, and a total porosity of 60% is obtained.

[0075] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing an iron-aluminum multi-level porous material, characterized in that: The following steps are involved: The iron powder, aluminum powder and molten paraffin are mixed and stirred, and then magnesium nitride powder is added and stirred evenly, and the molten paraffin is crushed after cooling and solidifying, and then put into a mold for compression molding, and then the molded green compact is vacuum sintered to obtain an iron-aluminum multi-level porous material; The particle size of the magnesium nitride powder is larger than that of the iron powder and the aluminum powder.

2. The method for preparing an iron-aluminum multi-level porous material according to claim 1, characterized in that: The iron powder and aluminum powder are Fe 1-x -Al x The ingredients are prepared in a ratio of atomic percentage, where x is 22.5%~76.5%.

3. The method for preparing an iron-aluminum multi-level porous material according to claim 1, characterized in that: The mass ratio of the iron-aluminum powder mixture to the molten paraffin is 2-6:1, and the mass ratio of the magnesium nitride powder to the iron-aluminum powder mixture is 2-4:

5.

4. The method for preparing an iron-aluminum multi-level porous material according to claim 1, characterized in that: The particle size of the iron powder and the aluminum powder is 1-100 μm, and the particle size of the magnesium nitride powder is 500-1000 μm.

5. The method for preparing an iron-aluminum multi-level porous material according to any one of claims 1 to 4, characterized in that: Vacuum sintering method The following steps are involved: S1, first raise the temperature to a temperature above the boiling point of paraffin, and keep the temperature at this temperature for more than 1 hour; S2, then continue to heat up to the temperature of solid diffusion of iron and aluminum, and keep the reaction at this temperature for 0.5h~5h; S3, then continue to raise the temperature to above the melting point of aluminum, but not exceeding the temperature at which magnesium nitride begins to sublime, and keep the reaction at this temperature for 0.5h~3h; S4, then continue to raise the temperature to the sublimation and decomposition temperature of magnesium nitride, and keep the reaction at this temperature for 1 to 6 hours.

6. The method for preparing an iron-aluminum multi-level porous material according to claim 5, characterized in that: In step S1, the temperature is increased to 400-500°C at a heating rate of 1°C / min-5°C / min.

7. The method for preparing an iron-aluminum multi-level porous material according to claim 5, characterized in that: In step S2, the temperature is increased to 500-660°C at a heating rate of 1°C / min-5°C / min.

8. The method for preparing an iron-aluminum multi-level porous material according to claim 5, characterized in that: In step S3, the temperature is increased to 660-700°C at a heating rate of 1°C / min-5°C / min.

9. The method for preparing an iron-aluminum multi-level porous material according to claim 5, characterized in that: In step S4, the temperature is increased to 700-1100°C at a heating rate of 1°C / min-10°C / min.

10. The method for preparing an iron-aluminum multi-level porous material according to claim 5, characterized in that: The iron-aluminum multi-level porous material has a hollow structure, an open porosity of 60% to 62%, and a total porosity of 65% to 70%.

Citation Information

Patent Citations

  • Method for manufacturing porous body

    CN101473055A

  • Method for removing magnesium nitride from porous aluminum nitride or porous gallium nitride particles

    CN102219195A

  • Preparation method of raw material for porous high-purity aluminum nitride

    CN111847402A

  • Porous magnesium alloy with through hole structure prepared by reactive sintering powder metallurgy method and preparation method of porous magnesium alloy

    CN112846184A

  • Preparation method of iron-aluminum intermetallic compound porous material

    CN112853139A